Photocatalytic splitting of CS2 to a carbon-sulfur polymer and S8 catalyzed by a bimetallic ruthenium(II) compound with a tertiary amine binding site - towards photocatalytic splitting of CO2? - Livanov, Konstantin; Madhu, Vedichi; Balaraman, Ekambaram; Shimon, Linda J. W.; Diskin-Posner, Yael; Neumann, Ronny (Inorganic Chemistry, 2011)
The catalytic photocleavage of CS2 to S8 and a (CxSy)n polymer with visible light using a dinuclear ruthenium(II) compound with a bipyridine units for photoactivity and a vicinal tertiary amine binding site for CS2 activation was studied. The catalyst was characterized by X-ray diffraction, 1H NMR, and 13C NMR, ESI-MS and elemental analysis. CS2 photocleavage was significant (240 turnovers, 20 h) to yield isolable S8 and a (CxSy)n polymer. A mononuclear catalyst or one without an amine binding site showed significantly less activity. XPS of the (CxSy)n polymer showed a carbon/sulfur ratio ∼1.5–1.6 indicating that in part both C–S bonds of CS2 had been cleaved. Catalyst was also included within the polymer. The absence of peaks in the 1H NMR verified the (CxSy)n nature of the polymer, while 13C NMR and IR indicated that the polymer had multiple types of C–S and C–C bonds.

PNN-Ru pincer complexes based on phosphinated 2,2’-dipyridinemethane- and 2,2’-oxobispyridine. metal-ligand cooperation in cyclometallation and catalysis - Barrios-Francisco, Rigoberto; Balaraman, Ekambaram; Diskin-Posner, Yael; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2013)
The synthesis of novel PNN ruthenium pincer complexes based on 2,2′-dipyridinemethane phosphine derivatives, as well as on 2,2′-oxobispyridine phosphine ligands, and their reactivity toward dearomatization and cyclometalation are described. The dearomatized compounds 7a,b undergo cyclometalation to yield complexes 8a,b. In order for cyclometalation to proceed, the coordination sphere around the Ru center has to rearrange, and this depends on the flexibility of the system, showing that the cyclometalation is qualitatively faster in the case of the dimethyl derivative 7a than in the case of the spyrocyclopentyl derivative 7b. The cyclometalation occurs diastereoselectively and leads to only one diastereomer of the cyclometalated compounds. In the case of the 2,2′-oxobispyridine complex 6c, the dearomatized complex was too unstable to be isolated; however it was possible to isolate and characterize a stable dicarbonyl-dearomatized ruthenium(II) complex, 9c, when the deprotonation was performed under a CO atmosphere. Dearomatization of 6a under CO also led to dicarbonyl-dearomatized ruthenium(II) complex 9a, which slowly rearranged into the dicarbonyl-aromatized ruthenium(0) complex 10a. These complexes were tested in catalytic alcohol–amine coupling, esterification of primary alcohols, and hydrogenation of secondary amides. Moderate activity was observed in hydrogenation of amides to alcohols and amines and low activity in the other transformations, owing mainly to the formation of stable cyclometalated compounds.

Predesigned metal-anchored building block for in situ generation of Pd nanoparticles in porous covalent organic framework: application in heterogeneous tandem catalysis - Bhadra, Mohitosh; Sasmal, Himadri Sekhar; Basu, Arghya; Midya, Siba P.; Kandambeth, Sharath; Pachfule, Pradip; Balaraman, Ekambaram; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2017)
The development of nanoparticle-polymer-hybrid-based heterogeneous catalysts with high reactivity and good recyclability is highly desired for their applications in the chemical and pharmaceutical industries: Herein, we have developed a novel synthetic strategy by choosing a predesigned metal-anchored building block for in situ generation of metal (Pd) nanoparticles in the stable, porous, and crystalline covalent organic framework (COF), without using conventional reducing agents. In situ generation of Pd nanoparticles in the COF Skeleton is explicitly confirmed' from PXRD, XPS, TEM images, and N-15 NMR spectral analysis. This hybrid material is found to be an excellent reusable heterogeneous catalyst for the synthesis of biologically and pharmaceutically important 2-substituted benzofurans from 2-bromophencils and terminal alkynes via a tandem process with the turnover number up to 1101. The heterogeneity of the catalytic process is unambiguously verified by a mercury poisoning experiment and leaching test. This hybrid material shows superior catalytic performance compared to commercially available homogeneous as well as heterogeneous Pd catalysts.

Pd(II)-Catalyzed gamma-C(sp(3))-H alkynylation of amides: selective functionalization of R chains of amides (RC)-C-1(O)NHR - Landge, Vinod G.; Parveen, Ayisha; Nandakumar, Avanashiappan; Balaraman, Ekambaram (Chemical Communications, 2018)
The gamma C(sp(3))-H bond alkynylation of R chains of amides (RC)-C-1(O)NHR, a fundamental class of synthetic substrates, has not been accomplished to date. Here, the first example of palladium(ii)-catalyzed alkynylation of an unactivated gamma C(sp(3))-H bond of alkyl amides (cyclic, linear, and amino acids) is reported. The kinetic experiment shows that the rate of the reaction depends on the coupling partners and the amides. Late-stage diversification of alkynylated amides was developed by utilizing amine and alkyne functionalities.

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.

Photocatalysis enabling acceptorless dehydrogenation of diaryl hydrazines at room temperature - Sahoo, Manoj K.; Saravanakumar, Krishnasamy; Jaiswal, Garima; Balaraman, Ekambaram (ACS Catalysis, 2018)
Aromatic azo compounds are privileged structural motifs, and they exhibit a myriad of pharmaceutical as well as industrial applications. Here, we report a catalytic acceptorless dehydrogenation of diarylhydrazine derivatives to access a wide variety of aryl-azo compounds with the removal of molecular hydrogen as the sole byproduct. This distinctive reactivity has been achieved under dual catalytic conditions by merging the visible-light active [Ru(bpy)(3)](2+) as the photoredox catalyst and Co(dmgH)(2)(py)Cl as the proton-reduction catalyst. The reaction proceeds smoothly under very mild and benign conditions and operates at ambient temperature. This dual catalytic approach is highly compatible with many different functional groups and has a broad substrate scope. We have also demonstrated the reversible hydrogen storage and release phenomenon on hydrazobenzene/azobenzene couple to show the utility of these compounds as hydrogen storage materials. Further diversification of azobenzene was shown by a transition metal-catalyzed azo-group-directed ortho-C-H bond functionalization.
Keywords: acceptorless dehydrogenation; Azo benzene; dual catalysis; Hydrogen; photoredox catalysis

Phosphine-free manganese(II)-catalyst enables acceptorless dehydrogenative coupling of alcohols with indoles - Yadav, Vinita; Balaraman, Ekambaram; Mhaske, Santosh B. (Advanced Synthesis & Catalysis, 2021)
Herein, an air-stable, molecularly defined NNN-Mn(II) pincer complex catalyzed acceptorless dehydrogenative coupling of alcohols with indoles is reported. A wide variety of symmetrical and unsymmetrical bis(indolyl)methane derivatives as well as some structurally important products such as Vibrindole A, Turbomycin B alkaloid, Antileukemic, and Anticancer agents were synthesized. Mechanistic studies illustrate the importance of the NH moiety in the complex and the crucial role of metal-ligand cooperation during catalysis.
Keywords: acceptorless dehydrogenation; Alcohol; Indole; manganese; phosphine-free